IMPLEMENTATION OF THE POLICY OF FOSTERING STREET CHILDREN IN MAKASSAR CITY (CASE STUDY ON THE MAKASSAR CITY SOCIAL SERVICE) - Murdi, Muthmainnah; Aslinda, Andi; Niswaty, Risma (Universitas Negeri Makassar, 2025)
This study aims to determine the implementation of the street child development policy in Makassar City implemented by the Makassar City Social Office. Policy implementation is an administrative activity carried out after a policy is ratified. The policy of fostering street children in Makassar City is regulated by a regulation contained in Regional Regulation Number 2 of 2008 concerning the development of street children in Makassar City. This research uses a descriptive qualitative approach that examines objects and reveals existing phenomena contextually through data collection obtained by looking at dimensions as interrelated units of study objects to further photograph social situations thoroughly and deeply. The study was conducted at the location of the Makassar City Social Office and the Social Service's Protection and Trauma Center (RPTC). The research was conducted with a focus on six dimensions that become a benchmark for optimal policy implementation, namely policy standards/measures and objectives, policy sources, characteristics of implementing agencies/agencies, communication between related organizations, attitudes of implementers, and economic, social, and cultural environments. The results showed that the implementation of the street child development policy at the Makassar City Social Office based on these six dimensions has not been optimal due to dimensions that have not been optimally implemented as a whole due to several obstacles faced. The policy of fostering street children is important to be implemented optimally considering that it is the obligation and responsibility of the state and government.